Comparative Analysis of the Economic Development Paths of Hungarian Counties - Kocziszky, György; Szendi, Dóra (Public Finance Quarterly, 2021)
The literature has analysed economic growth issues for nearly 250 years, and formulated theories, indicators and calculations. The same cannot be observed for economic development. This is reflected, among others, by the fact that some publications still use the terms economic growth and development synonymously. In the present study, the authors, after a brief theoretical overview of economic development and path dependency, quantified the economic development of 19 Hungarian counties and the capital city using a complex index, and then examined the changes in the index between 1995 and 2019. The final part of the paper analyses the expected similarities and differences in the development paths up to 2024. The counties have followed different development paths over the last 25 years, a trend that is also reflected over the forecast horizon. The development trajectories of the counties are more sensitive to shocks than the paths of specific GDP output, due to global, macro and local shocks that occur from time to time.